Preoperative biliary drainage in severely jaundiced patients with pancreatic head cancer: A retrospective cohort study. Issue 11 (November 2022) - van Gils, Luuk; Verbeek, Romy; Wellerdieck, Nienke; Bollen, Thomas; van Leeuwen, Maarten; Schwartz, Matthijs; Vleggaar, Frank; Molenaar, I.Q. (Quintus); van Santvoort, Hjalmar; van Hooft, Janine; Verdonk, Robert; Weusten, Bas; et al.
Abstract: Background: Guidelines recommend against preoperative biliary drainage (PBD) in patients with pancreatic head cancer if bilirubin levels are <250 μmol/l. However, patients with higher bilirubin levels undergo PBD, despite the lack of supporting evidence. This study aims to evaluate outcomes in patients with a bilirubin level ≥250 and < 250. Methods: Patients were identified from databases of 3 centers. Outcomes were compared in patients with a bilirubin level ≥250 versus <250 both at the time of diagnosis and directly prior to surgery. Results: 244 patients were included. PBD was performed in 64% (123/191) with bilirubin <250 at diagnosis and 91% (48/53) with bilirubin ≥250. PBD technical success (83% vs. 81%, p = 0.80) and PBD related complications (33% vs. 29%, p = 0.60) did not differ between these groups. Analyzing bilirubin levels ≥250 versus <250 directly prior to surgery, no differences in severe postoperative complications and mortality were found. Conclusions: In patients with a pancreatic head cancer, PBD technical success and complications, and severe postoperative complications did not differ between patients with a bilirubin level ≥250 and < 250. Our study does not support a different approach regarding PBD in patients with severe jaundice.